If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + -1x) = 5(4x + -1) (3 * 2 + -1x * 2) = 5(4x + -1) (6 + -2x) = 5(4x + -1) Reorder the terms: 6 + -2x = 5(-1 + 4x) 6 + -2x = (-1 * 5 + 4x * 5) 6 + -2x = (-5 + 20x) Solving 6 + -2x = -5 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 6 + -2x + -20x = -5 + 20x + -20x Combine like terms: -2x + -20x = -22x 6 + -22x = -5 + 20x + -20x Combine like terms: 20x + -20x = 0 6 + -22x = -5 + 0 6 + -22x = -5 Add '-6' to each side of the equation. 6 + -6 + -22x = -5 + -6 Combine like terms: 6 + -6 = 0 0 + -22x = -5 + -6 -22x = -5 + -6 Combine like terms: -5 + -6 = -11 -22x = -11 Divide each side by '-22'. x = 0.5 Simplifying x = 0.5
| 8x-2=11x+7 | | .5(5x+4)-.33(x+7)=4 | | 81+8=6+5 | | 3x+15=33 | | 8-81=5-6 | | 3(y-8)=4(2y+9) | | 2x=7+-43-8x | | 9-p=4p-11 | | 2x-10=7x-11 | | 6a-16+6a-15+6a+7=48 | | -4x+6+x=-2x+x-10 | | -3x-8+x=-4x+-10 | | c/4=16 | | x-(-12)=2 | | 2(x+10)-5(2-x)+3=0 | | 81-4x^2=0 | | x-(-8)=-28 | | (x^2-11+19-x)(-10)= | | (3x-5)+(3x+5)+x=180 | | 4m^3-9=23 | | x-(-1)=50 | | 3.2b+8=20 | | 2+6x-3-3x=0 | | 22=4(5y-2) | | x-(-5)=10 | | x+(x+5)+x+(x+5)=26 | | 19=17-2x | | 9-5t=3t+18 | | 5x+4=13x-68 | | 9x^2+16=24x | | 3p^2+5=32 | | 19x-7=1+17x |